Radioactive waste treatments by using zeolites. A short review. (July 2021) - Jiménez-Reyes, M.; Almazán-Sánchez, P.T.; Solache-Ríos, M.
Abstract: Radionuclides in the environment is an important issue, many techniques have been developed for the removal of radionuclides from the environment. One of those techniques is the adsorption and natural and synthesized materials have been used to remove different radionuclides from water. The adsorbents used for removal of radionuclides should have high retention capacity and they should be resistant to radiation. One of the natural materials used is the zeolites due to its high ion exchange capacities, adsorption efficiency, resistance to radiation and abundance. The present review describes the advances made on radioactive waste treatments using zeolites as adsorbents, the elements: cesium, strontium, cobalt, molybdenum, uranium, plutonium, americium, samarium, and europium were selected according to their nuclear importance and their presence in the environment. Firstly, a brief description of the zeolites is given and then a review on the separation of these radionuclides from water by using zeolites is presented. Highlights: Adsorption is an efficient method to treat nuclear wastes. Zeolite are versatile materials used as adsorbents to treat nuclear wastes. Metals present in nuclear wastes can be removed by zeolites.